Pelestarian Budaya Tahlil Kepada Anak Muda Melalui Organisasi IPNU-IPPNU Di Kecamatan Puring - Febriany, Febriany; Zahna, Lutfi Raizatul; Nisa, Istiti Sakinatun; Sari, Reza Kurnia Citra (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2024)
The preservation of the tahlil tradition among young people through the IPNU-IPPNU organization in Puring District is an important effort to maintain a long-standing religious tradition in the community. Tahlil, which consists of the recitation of "laa ilaaha illallah," salawat, tasbih, and Qur'anic verses, followed by a prayer for the deceased, holds high spiritual and social value. However, with the changing times, this tradition faces challenges, especially in terms of youth participation. The IPNU-IPPNU organization, as a student-based platform, plays a key role in teaching and involving young people in tahlil activities, ensuring that these cultural values remain alive and relevant. This study aims to explore the role of IPNU-IPPNU in preserving the tahlil tradition among the youth in Puring District. The research uses a qualitative method with a field study approach, involving observation and interviews with the IPNU-IPPNU leadership and members. The results are expected to provide insights into effective strategies for engaging youth in the preservation of the tahlil tradition.